2021
DOI: 10.1002/mus.27236
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion of mean consecutive differences in single‐fiber electromyography increases diagnostic sensitivity for myasthenia gravis

Abstract: Introduction: In this study we aimed to investigate the dispersion of mean consecutive difference (MCD) of concentric needle jitter studies of patients with myasthenia gravis (MG) and its effect on diagnostic sensitivity for MG.Methods: One hundred fifty-three patients, including 76 patients with MG and 77 controls with possible MG who later received another diagnosis, underwent stimulated concentric needle jitter studies of the frontalis muscle. MCD mean, standard deviation (SD), and coefficient of variation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
4
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 20 publications
3
4
1
Order By: Relevance
“…We found that the optimal cutoffs for SD according to Youden statistics were 13.5 microseconds for the OO, 12.6 microseconds for the FRO, and 11.8 microseconds for the EDC, whereas the areas under the receiver-operating characteristic curves were 0.89, 0.87, and 0.89 respectively. Similar to the results of Kojima et al, 5 these values were characterized by high sensitivity and specificity, which was comparable to those resulting when using the number of outliers as a criterion (Table 1). Abnormal jitter is not specific to MG, but to disturbed neuromuscular transmission of any cause.…”
Section: The Dispersion Of Individual Jitter Values Is a Sensitive Di...supporting
confidence: 88%
See 4 more Smart Citations
“…We found that the optimal cutoffs for SD according to Youden statistics were 13.5 microseconds for the OO, 12.6 microseconds for the FRO, and 11.8 microseconds for the EDC, whereas the areas under the receiver-operating characteristic curves were 0.89, 0.87, and 0.89 respectively. Similar to the results of Kojima et al, 5 these values were characterized by high sensitivity and specificity, which was comparable to those resulting when using the number of outliers as a criterion (Table 1). Abnormal jitter is not specific to MG, but to disturbed neuromuscular transmission of any cause.…”
Section: The Dispersion Of Individual Jitter Values Is a Sensitive Di...supporting
confidence: 88%
“…Our data underscore the clinical utility of the method introduced by Kojima et al, 5 suggesting that the variability of signal transmission at the motor endplate inherent in MG can be reflected in the dispersion of individual jitter values in a single muscle SFEMG study. Its concordance with the established measure of jitter dispersion, namely the number of outliers in a single SFEMG session, is high but not perfect (Table 2).…”
Section: The Dispersion Of Individual Jitter Values Is a Sensitive Di...supporting
confidence: 67%
See 3 more Smart Citations